Dental follicle infection following a dog bite - G. WRIGHT, M. L. MUIR, R. BRYAN, A. J. SMITH, & M. T. HOSEY (Paediatric Dentistry, 2006)
Animal bite wounds and their subsequent infection are relatively common. Incidence rates for dog bites are significantly higher among children aged 0–9 years, especially among boys. Although bite wounds may initially look innocuous, they frequently lead to serious infection with a potential for life-threatening complications.